Making a difference : a comparative study of the rules, responsibilities and perspectives of teacher aides in primary and secondary schools in New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Palmerston North, New Zealand - Stevenson, Mignon Josette (Massey University, 2012)
Teacher aides are used in the majority of primary and secondary schools in New Zealand to assist teachers in supporting students with many diverse needs. They play a crucial role in the extent to which students with diverse needs are fully included in mainstream schools. The nature of their work has changed over the years, so as to meet the goals of inclusive education. The work of teacher aides is primarily related to the different structures operating within primary and secondary schools. This study used mixed methods methodology to compare the roles, responsibilities and perspectives of 21 teacher aides working in primary and secondary schools in a single geographical area on the North Island of New Zealand. Questionnaires, job descriptions and semi-structured interviews were used to gain an understanding of the roles, responsibilities and perspectives of teacher aides in both types of schools. The study found that teacher aides generally carried out a diverse range of tasks, provided support at different levels and had high levels of responsibility. The main themes that were identified related to teacher aide training and professional development, relationships, personal and cultural factors, challenges, funding and school systems. The study found that there were more similarities than differences between teacher aides working in primary and secondary schools and that the teacher aides’ roles and responsibilities were related to perceived ability to include students with diverse needs. The study concludes with implications for further research, policy and practice. These focus on primary and secondary teacher aide training and the inclusion of a wider variety of perspectives and factors related to the ability of teacher aides to make a difference for students with diverse needs in New Zealand.
Keywords: Teacher aides; Primary school teaching; Secondary school teaching